Chlamydia trachomatis proctitis masquerading as carcinoma rectum: First case report from India - Benu Dhawan; Govind Kumar Makharia; Deepak Juyal; Sujeesh Sebastian; Riti Bhatia; Neena Khanna (Wolters Kluwer Medknow Publications, 2017)
While proctitis is caused both by infectious and noninfectious causes, infectious causes are acquired typically sexually. Chlamydia trachomatis, which is the most frequent bacterial pathogen causing sexually transmitted infections worldwide, is one of the causative agents of proctitis. We report a case history of a bisexual male who presented to us with rectal bleeding. The colonoscopy showed a nodular ulcerated lesion in the rectum suggestive of rectal malignancy, but biopsies from rectal mass did not reveal malignancy. A rectal biopsy was positive for C. trachomatis by polymerase chain reaction assay, and a diagnosis of C. trachomatis proctitis was made. Considering the invasive anorectal disease and patient's sexual history, he was treated with prolonged doxycycline therapy as per Centres for Disease Control and Prevention's treatment recommendation for lymphogranuloma venereum. A high index of clinical suspicion along with appropriate microbiological testing can clinch the diagnosis of C. trachomatis infection.